Ad hoc accounting and accountability for the local governance of an epidemic crisis: the yellow fever in Cádiz in 1800 - Capelo, Mariló; Araújo, Pedro (De Computis, Revista Española de Historia de la Contabilidad., 2019)
This paper aims to extend the knowledge about how ad hoc accounting and accountability practices arose and were used in the past to face a situation of crisis in the context of local government. With this purpose, it addresses a health public problem in a specific context, the yellow fever epidemic in Cadiz in 1800. The specific characteristics of the setting, where acquaintance with accounting was usual, allow setting the following specific objectives: (1) to explain the genesis of the accountability systems and the accounting itself used for local government management of the epidemic and (2) to explore the versatility and plasticity that accounting background provides to the records produced in this context. To accomplish them, primary sources as well as publications of the time have been considered. The evidence obtained shows that both an accountability system and a basic bookkeeping system influenced by the local accounting and medical background arose in the local context. Moreover, the findings suggest that the generalized accounting background promoted the self-serving use and interpretation of the records by local government, local Church, trade association and medical profession. The value that local society attributed to accounting books was important in this sense.